A STUDY ON DNA FINGERPRINTING OF AREOLATED GROUPER (Epinephelus areolatus) USING RAPD ANALYSTS - Andi Parenrengi; Lokman Shamsudin; Patimah lsmail; Nakisah Mat Amin (Indonesian Fisheries Research Journal, 2002)
This study reports the application of Random Amplified Polymorphic DNA (RAPD) technique in establishment of DNA fingerprinting of areolated grouper, Epinephelus areolatus, an economically tmportant fish species of the subfamily Epinephelinae (popularly known as grouper)